The Influence of Testimony Video in Early Detection of Cervical Cancer - Siti Masitoh; Mardeyanti Mardeyanti (Poltekkes Kemenkes Jakarta III, 2020)
The high incidence of cervical cancer in Indonesia is up to almost 80%. The cause of action is needed early detection through examination visual inspection with acetic acid/pap smear as a precaution to handling this disease. Women have avoided early detection through pap smear due to a lack of knowledge. The study's purpose was to determine the effect of health education with the module and video testimonials on increasing knowledge, attitude, and behavior in the early detection of cervical cancer by pap smear in Community Health Centers District Cipayung. This study uses a Quasi Experiment with pretest-posttest design in two groups, consisting of groups with a module method and groups by watching testimonial videos. Data obtained from questionnaires for knowledge, attitude, and behavior. The total samples are 70. Each group is 35 respondents. The results showed in the module group, and there were differences in knowledge before and after health education (p-value 0,000) and behavior (0.029). There are differences in knowledge (p-value 0.046) and behavior (0,000). This study also shows differences in behavior after getting health education between modules and video testimonials (p-value 0.003). Education of respondents influences knowledge (p-value 0,000). Health education using video testimonials increases attitudes and behaviors towards the early detection of cervical cancer.